COMPARISON BETWEEN LIVE-ACTION AND ANIMATION VERSION OF DISNEY MULAN USING DISNEY FORMULA - Berlian Puspa Negara (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Mulan is a movie that has two versions in animation and live-action. This research aims to reveal the similarities and differences between both versions using the Disney formula. To show the problem of this research, it uses the Disney formula by Xu and Tian (2013). As the study results, good and bad characters can identify the visual image through behavior and dialogue. The helper is not only for the heroin, but the enemy also gets a helper in live-action. The love line in the live-action version is bittersweet. The theme song is the same, jokes, the stars, and the voice is original by the stars. The stars that appear in both versions are different. Disney used Mulan’s story using the Disney formula to create similarities and differences in both versions.